Recreational economic value of the Perlis State Park, Malaysia: an application of zonal travel cost model - Mohammad Afandi, Syamsul Herman; Shuib, Ahmad; Sridar, Ramachandran; Yacob, Mohd Rusli (Universiti Putra Malaysia Press, 2013)
Perlis State Park is known for recreational activities. Since there is no significant income from timber production for the state of Perlis, outdoor recreation provides the alternative source of income. Since managing a state park costs substantially, assessment of recreational uses justifies the initial cost. This paper, using the semi-aggregated travel cost method, estimates the recreational value of Perlis State Park for Malaysian domestic visitors. The recreational value of the park is estimated at RM5,340,642.48. The value derived from the study contributes to the stakeholders` assessment of the intangible value of the park to justify the ecotourism developmental cost. The valuation of the recreational activities in public parks reveals the non-market economic value of the park under certain type of management. This paper also emphasises on the importance of maintaining visitor arrivals as a means to sustain the recreational value.